2017
DOI: 10.4103/ijccm.ijccm_454_16
|View full text |Cite
|
Sign up to set email alerts
|

A study of 24 patients with colistin-resistant Gram-negative isolates in a tertiary care hospital in South India

Abstract: Background:As the use of colistin to treat carbapenem-resistant Gram-negative infections increases, colistin resistance is being increasingly reported in Indian hospitals.Materials and Methods:Retrospective chart review of clinical data from patients with colistin-resistant isolates (minimum inhibitory concentration >2 mcg/ml). Clinical profile, outcome, and antibiotics that were used for treatment were analyzed.Results:Twenty-four colistin-resistant isolates were reported over 18 months (January 2014-June 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
36
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(49 citation statements)
references
References 24 publications
12
36
1
Order By: Relevance
“…Infection with colistin-resistant organisms is associated with a substantially increased risk for mortality, and options for treatment are limited (9)(10)(11)(17)(18)(19)(20). Prior studies have typically been relatively small or limited in scope, either following a relatively small number of patients (9,10,17,18,24,26,(30)(31)(32)(33) or focusing on a single organism (16,21,22,27), and none have resulted in a clinically meaningful prediction tool. Our score can be calculated by providers at the time of decision making without the help of a computer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Infection with colistin-resistant organisms is associated with a substantially increased risk for mortality, and options for treatment are limited (9)(10)(11)(17)(18)(19)(20). Prior studies have typically been relatively small or limited in scope, either following a relatively small number of patients (9,10,17,18,24,26,(30)(31)(32)(33) or focusing on a single organism (16,21,22,27), and none have resulted in a clinically meaningful prediction tool. Our score can be calculated by providers at the time of decision making without the help of a computer.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of colistin resistance among GNRs has been increasing over the past 2 decades, particularly among isolates of Klebsiella pneumoniae (8,10,(12)(13)(14)(15)(16), limiting the potential utility of colistin. Infection with Col r GNRs is associated with a higher mortality than infection with colistin-susceptible (Col s ) isolates (9,10,(17)(18)(19)(20), making the rapid identification of resistance important. However, the early identification of Col r GNRs is challenging.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Colistin resistance was associated with higher resistance rates to quinolones, fosfomycin and tobramycin, but not carbapenem resistance. Carbapenem-resistant Enterobacteriaceae are known to have concurrent resistance to colistin, fosfomycin and quinolones [ 16 - 18 ], but resistance clusters without concomitant carbapenem resistance have not been described so far and its role and aetiology remains unclear. High rates of colistin resistance in human samples have mainly been reported in countries with high proportions of carbapenem-resistant Gram-negative bacteria and subsequent widespread use of colistin in healthcare settings.…”
Section: Discussionmentioning
confidence: 99%
“…Reports of returning chloramphenicol susceptibility are increasing 9 . Studies in Indian hospitals have found that 68% of MDR Gram-negative bacteria 12 and 62.5% colistin-resistant Gram-negative bacteria 13 were susceptible to chloramphenicol. In Malawi chloramphenicol was used in combination with benzylpenicillin as the first-line therapy in the empirical management of suspected sepsis, until 2015 4 .…”
Section: Introductionmentioning
confidence: 99%